Progressive Analytics Diffusions: Rewiring our Software - Liz Wanless (Journal of Applied Sports Management, 2022)
The sport industry is no stranger to the pursuit of innovation (Slack & Thurston, 2021). The sport analytics realm represents the continual emergence of innovation diffusion curves. This essay shows how innovating both research and education in response to diffusion curves in sport analytics, we can create the space to not only keep but also generate pace.
Keywords: sport analytics; sport management; analytics